Optimizing synergies: Effective strategies for integrating economic and environmental interests in sustainable development - Shukurova Shoxina (E3S Web of Conferences)
As the global economy expands, the tension between economic growth and environmental sustainability intensifies. Traditional ecologicaleconomic systems often struggle to balance these competing interests, leading to conflicts that undermine both environmental quality and economic stability. This study aims to explore effective strategies for harmonizing economic and environmental interests within sustainable development frameworks. We seek to identify and address the inherent contradictions in current ecological-economic systems and propose integrative approaches to mitigate these conflicts. We conducted a theoretical analysis of ecological and economic relations, examining case studies and existing literature to identify key areas of conflict and synergy. Conceptual frameworks were developed to illustrate the causal relationships between economic activities and environmental impacts, with a focus on global pollution trends and their implications for sustainable development. The analysis reveals that conflicts between economic and environmental interests are primarily due to the inadequacies in current ecologicaleconomic systems. The study identifies several critical areas where better integration can enhance system stability, including improved resource management practices, enhanced regulatory frameworks, and the adoption of ecologically oriented economic strategies. Addressing the conflicts between economic and environmental interests requires a paradigm shift towards an ecologically clean society.